GBS-derived SNP catalogue unveiled wide genetic variability and geographical relationships of Italian olive cultivars. Issue 1 (December 2018) - D'Agostino, Nunzio; Taranto, Francesca; Camposeo, Salvatore; Mangini, Giacomo; Fanelli, Valentina; Gadaleta, Susanna; Miazzi, Monica; Pavan, Stefano; di Rienzo, Valentina; Sabetta, Wilma; Lombardo, Luca; Zelasco, Samanta; et al.
Abstract Information on the distribution of genetic variation is essential to preserve olive germplasm from erosion and to recover alleles lost through selective breeding. In addition, knowledge on population structure and genotype–phenotype associations is crucial to support modern olive breeding programs that must respond to new environmental conditions imposed by climate change and novel biotic/abiotic stressors. To further our understanding of genetic variation in the olive, we performed genotype-by-sequencing on a panel of 94 Italian olive cultivars. A reference-based and a reference-independent SNP calling pipeline generated 22, 088 and 8, 088 high-quality SNPs, respectively. Both datasets were used to model population structure via parametric and non parametric clustering. Although the two pipelines yielded a 3-fold difference in the number of SNPs, both described wide genetic variability among our study panel and allowed individuals to be grouped based on fruit weight and the geographical area of cultivation. Multidimensional scaling analysis on identity-by-state allele-sharing values as well as inference of population mixtures from genome-wide allele frequency data corroborated the clustering pattern we observed. These findings allowed us to formulate hypotheses about geographical relationships of Italian olive cultivars and to confirm known and uncover novel cases of synonymy.